CTD measurements at 8 stations of Senckenberg cruise SEN2212 - Mareike Kampmeier; Everardo González; Jens Greinert (PANGAEA, 2023)
CTD measurements taken during the Senckenberg cruise SEN2212 for the CONMAR project of the DAM research mission "Protection and Sustainable Use of Marine Areas". All measurements were taken the 3rd of May 2022 between Jade and Wangerooge in the German North Sea coast using a Sea And Sun CTD. Further data processing was undertaken using Sea And Sun extquotesingles SDA SST software. Depth was calculated from pressure and latitude according to Fofonoff & Millard (1983) using python seawater 3.3.4 module.